Revealing the Impact of Job Satisfaction on PT. Nusantara Medika Utama Employee Performance : Mengungkap Dampak Kepuasan Kerja pada Kinerja Karyawan PT. Nusantara Medika Utama - Amara Adinda Diasputri; Wiwik Handayani (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This study examines the relationship between job satisfaction and employee performance at PT. Nusantara Medika Utama, a company in the healthcare sector. The primary aim of this study is to understand the extent to which employee job satisfaction influences productivity, work quality, and innovation within the organization. Using a descriptive qualitative approach, data was collected from the analysis of the company's internal documents, interviews with employees, and a job satisfaction survey. The survey results indicate that 83.07% of employees feel very satisfied with their jobs. The main findings suggest that job satisfaction has a significant impact on performance improvement, including aspects of productivity, service quality, and creativity. However, there are several challenges that need to be addressed, such as compensation adjustments, career development opportunities, and cross-divisional communication. PT. Nusantara Medika Utama has designed strategic solutions to enhance job satisfaction, including salary policy adjustments, improved workplace facilities, and ongoing training programs. With the implementation of these solutions, the company is expected to create a better work environment and enhance overall performance.